EVALUATING THE IMPACT OF MICROPLASTICS ON Catla catla IN POND WATERS OF SARGODHA USING FTIR SPECTROSCOPY (Journal of Medical & Health Sciences Review, 2025)
Microplastics-pieces of plastic smaller than 5 millimeters-are now seen as a serious pollutant in freshwater systems, especially in aquaculture ponds. This study looks at how many of these tiny particles are floating in the water around Sargodha, Pakistan, and whether they end up in the meat of Catla catla, a popular local fish. Most scientific attention has gone to oceans, leaving little information about South Asian freshwater farms. Earlier work has shown that microplastics can hurt habitats, throw off food webs, and carry harmful chemicals. By studying area ponds, this project begins to fill that knowledge hole and shows what the pollution could mean for people who eat the fish. To gather data, researchers took water and fish samples from five ponds-Chak No. 36, Chak No. 39, Chak No. 94, Chak No. 98, and Chak Asian Wala Gaoun-while following strict steps to avoid outside contamination. Experts then used FTIR (Fourier Transform Infrared) spectroscopy to sort different plastics and confirm how many particles were in the water and in fish tissue. FTIR readings highlighted the uniform presence of polyethylene, polypropylene, polystyrene, and polyethylene terephthalate in every sample tested. Fish meat contained more fragments and a wider mix of plastics than the surrounding water, pointing to bioaccumulation and potential travel up the food chain. Peak intensity and placement differed from one site to another, with Chak No. 36 expressing the heaviest burden.